Iron Protein Complex in Soybean Tempe - Mary Astuti (agriTECH, 1992)
In this study some characteristics of iron-protein complex in soybean tempe were investigated. Tempe was prepared by fermenting dehulled cooked soybeans at 30°C for 0; 24; 48; 72 and 96 hours, respectively. Tempe protein was extracted using Tris-maleate butfer at pH 6.5 and the extract was dialyzed in cellulose tube MM. 12,000. The residue was fractionated using Sepharose 6B/CI-6B gel filtration. The protein and iron distribution in those fractions and their molecular weight were determined. Results showed that fermentation increasing the number of protein fractions. The molecular weight of protein fractions was in the range of 5.000 - 70,000 daltons. Iron was distributed in all fraction measured. The percentage of protein and iron in fractions with molecular weight > 70,000 daltons decreased with longer fermentation time. Some of the small molecular weight of protein fractions failed to pass the cellulose membrane